(untitled) (Journal of the College of Education for Women, 2019)
Cash studies on Biography few self, compared to what feet of analysis and criticism in the other arts as (novel, short story, poetry, theater, painting), however, is a biographical articles in the relatively few Arabic literature as presented in the other Arts, has taken this Art greater opportunity in our literature with his Taha Hussein (days), or (my life) to Ahmed Amin, or Fadwa Toukan (a nice trip, and difficult journey), or Jabra Ibrahim Jabra in the (first well) or (Princess Street), which forms taken from the self point of departure the desire to write a CV to try to familiarize readers with the information possible to the same creator, the remainder (ego) is the axis basis in a CV, gradually, starting from childhood through youth and the end of Eholh, has methods beyond, and be endings open, according to the desire of the creator in the narrative Events way and how they aspire to.